Extensive Hand Thermal and Blast Injury From Electronic Cigarette Explosion: A Case Report - Satteson, Ellen S. (Hand (N Y), 2017)
Background: As the use of electronic cigarettes rises, more reports of injuries related to device explosion are surfacing. Methods: Presented here is the case of a 35-year-old man sustaining extensive thermal and blast injuries to his hand when the device exploded while he was holding it. He required multiple surgeries involving groin flap coverage, tendon transfer, and nerve grafting to optimize his postinjury function. Results: While much of his hand function has been restored, he has continued deficits in range of motion and sensation as a result of the incident. Conclusions: With increasing numbers of such injuries, hand surgeons must be aware of the blast mechanism involved so as to avoid missing deep soft tissue injury or disruption of deep structures, as demonstrated in this case.